Coumarin and quinolone action in archaebacteria: evidence for the presence of a DNA gyrase-like enzyme. - Sioud, M (1988)
The action of novobiocin and coumermycin (two coumarins which interact with the gyrB subunit of eubacterial DNA gyrase) and ciprofloxacin (a fluoroquinolone which interacts with the gyrA subunit of DNA gyrase) was tested on several archaebacteria, including five methanogens, two halobacteria, and a thermoacidophile. Most strains were sensitive to doses of coumarins (0.02 to 10 micrograms/ml) which specifically inhibit DNA gyrase in eubacteria. Ciprofloxacin inhibited growth of the haloalkaliphilic strain Natronobacterium gregoryi and of the methanogen Methanosarcina barkeri. In addition, ciprofloxacin partly relieved the sensitivity to coumarins (and vice versa). Novobiocin inhibited DNA replication in Halobacterium halobium rapidly and specifically. Topological analysis has shown that the 1.7-kilobase plasmid from Halobacterium sp. strain GRB is negatively supercoiled; this plasmid was relaxed after novobiocin treatment. These results support the existence in archaebacteria of a coumarin and quinolone target related to eubacterial DNA gyrase.